2017
DOI: 10.5301/tj.5000671
|View full text |Cite
|
Sign up to set email alerts
|

Primary Signet Ring Cell Carcinoma of the Pancreas with a Good Response to Chemotherapy: Case Report and Literature Review

Abstract: Significant tumor downsizing in our patient clearly demonstrates good response to neoadjuvant gemcitabine monotherapy. The optimal preoperative chemotherapy leading to tumor reduction and disease control in patients with borderline resectable and locally advanced pancreatic carcinoma is controversial, necessitating further randomized studies including combined chemoradiotherapy and multidrug combination regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…These tumors can be seen on CT scan of the abdomen as a discrete hyperdense (as in our case) or hypodense lesion in the pancreas . Case reports describe findings on CT which range from showing no significant changesto identification of a diffuse tissue mass involving the pancreas . Sakai T. et al reported a case of pancreatic SRCC detected as main pancreatic duct dilation, found primarily in the pancreatic body, with multiple mural nodules identified on CT scan …”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…These tumors can be seen on CT scan of the abdomen as a discrete hyperdense (as in our case) or hypodense lesion in the pancreas . Case reports describe findings on CT which range from showing no significant changesto identification of a diffuse tissue mass involving the pancreas . Sakai T. et al reported a case of pancreatic SRCC detected as main pancreatic duct dilation, found primarily in the pancreatic body, with multiple mural nodules identified on CT scan …”
Section: Discussionmentioning
confidence: 59%
“…From available case reports in the literature, the age at diagnosis of pancreatic SRCC ranged from 61 to 88 years. Mausam Patel et al, in their population‐based study, reported the mean age to be 66.6 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study using the Surveillance, Epidemiology, and End Results database from 2000 to 2014, the incidence of pancreatic SRCC is 0.4-0.5% among all cases of pancreatic carcinoma [1]. Among the eight cases reported thus far (Table 1) [4][5][6][7][8][9][10][11], surgical treatment with radical resection, pancreatoduodenectomy, and/or total pancreatomy could be performed in four cases, and there was only one case of borderline-resectable tumor treated with neoadjuvant chemotherapy with gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…FNA of PSRCCP has been reported to show abundant inflammatory cells, sometimes misleading the pathologists towards the diagnosis of pancreatitis, and sometimes delaying the definitive diagnosis until postmortem examination . Thus some authors suggest performing a core needle biopsy of the pancreatic mass with high suspicion for malignancy, if multiple attempts of FNA repeatedly yielded negative results …”
Section: Discussionmentioning
confidence: 99%